Operation and coordination mechanism of closed-loop supply chain considering corporate social responsibility behavior consciousness - A. K. M. Mohsin; Hongzhen Lei; Syed Far Abid Hossain; Hasanuzzaman Tushar; Mozaffar Alam Chowdhury; Mohammad Ebrahim Hossain (Cogent Business & Management, 2020)
The closed-loop supply chain (CLSC) management has become an important development strategy for many large enterprises, which reduces environmental pollution. This study is about the operation and coordination of third-party recycling CLSC considering the manufacturer's corporate social responsibility (CSR) behavior awareness and the retailer's profit donation as CSR investment. Based on the observations in industry, it is assumed that the CSR behavior of the manufacturer is to take consumer surplus as maximizing social welfare. At the same time, the retailer performs the CSR investment behavior to social welfare organizations. The CSR investment of retailers brings reputation and affects the market demand for new products. The results show that the CSR behavior awareness of manufacturers and the CSR investment of retailers have a mutual incentive effect and is conducive to expanding the market demand for new products and improving the recycling rate of waste products. The study constructs a third-party recycling closed-loop supply chain operation and coordination model. It analyzes both manufacturer's CSR awareness and retailer CSR investment to the closed-loop supply chain members. The findings are that both of them have a mutually stimulating effect, expanding the market demand for new products, increasing the recycling rate of waste and bringing higher social welfare.
Keywords: 650; closed-loop supply chain; CSR investment; CSR behavior awareness; "revenue- cost sharing" contract